Forecasting Short-Term Crude Oil Prices with a Deep Learning Approach - Vanitchakornpong, Kriangsak; Ananpalasak, Nipapan; Indra-Payoong, Nakorn; Sokai, Numchai (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 2 (2023): April-June 2023, 2023)
This paper presents a multi-layer neural network model to forecast short-term crude oil prices. The model is designed and developed for learning and analyzing the volatility of oil prices based on demand and supply fundamentals and sentiment data from online news. Potential keywords from the news regarding oil prices and price movements were grouped, pre-processed, and used as the neural network’s input features. The stochastic gradient descent and regularization techniques were applied for neural learning. Designing the neural network for our study includes three models: The Fundamentals Model (FDM), Single Word Model (SWM), and Combined Word Model (CWM). Experimental results achieved show that the proposed model is promising for crude oil price forecasting for the next 1, 2, 3, and 5 days with mean absolute percentage errors of less than 3% for all test cases. There were also unnoticeable forecasting errors using demand-supply fundamentals alone and with sentiment data. However, our experiments have shown that the CWM had a higher Goodness-of-Fit to the model, and R-squared value, indicating greater predictability than the FDM and SWM models. Keywords: Crude oil price, Sentiment data, Neural network, Short-term forecasting, Deep Feed Forward